Variability of ionospheric parameters during geomagnetic storms at a middle latitude station: Comparisons with IRI model - Mansilla, Gustavo Adolfo (2004)
This paper discusses the behavior of ionospheric parameters that were obtained from electron density profiles derived from ionograms recorded at El Arenosillo (37.1°N, 353.2°E; Dip = 52; Modip = 45.5) during some intense geomagnetic storms. The selected parameters are the critical frequency of the F2 layer, f o F2, the height of the peak electron density, h m F2, the thickness and shape parameters of the F2 layer, B0 and B1, and the integrated total electron content (ITEC). As a measure of the ionospheric disturbance during the storms the relative deviations of these parameters from their corresponding monthly medians has been calculated. All the parameters present changes during the storms. In general, increases during the main phase and first stage of the recovery phase are observed. The relative deviations of f o F2 and ITEC present similar temporal behavior (as during quiet geomagnetic conditions). Comparisons between f o F2 and ITEC with IRI 2001 model predictions show that the model significantly overestimates the ionospheric parameters mainly during the recovery phase of the storms.